2014
DOI: 10.1089/omi.2013.0064
|View full text |Cite
|
Sign up to set email alerts
|

Saliva: A Fluid of Study for OMICS

Abstract: Saliva is a fluid that can be collected easily and noninvasively. Its functions in the oral cavity are well known. Advances in molecular biology and technology, as well as research conducted by the various disciplines of omics (genomics, transcriptomics, proteomics, metabolomics, and metagenomics) have contributed to the identification and characterization of salivary components, including DNA, RNA, proteins, metabolites, and microorganisms. These biomolecules enter the saliva through extracellular and intrace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(60 citation statements)
references
References 90 publications
0
58
0
2
Order By: Relevance
“…These enzymes may also be involved in the initiation of digestion of food components in the oral cavity. The other major category of proteins identified were the transport/carrier proteins apolipoprotein B (APOB), albumin (ALB) and apolipoprotein H (APOH) that might have been detected in saliva through leakage from blood [34,35]. Calcium binding proteins such as calmodulin-like (CALML5), calcium binding protein 39 (CAB39), members of S100 family (S100A7, S100A8, S100A9, S100A11) and annexin family members (ANXA1, ANXA2, ANXA3) were also identified in saliva.…”
Section: Biological Process and Subcellular Localization Of Human Salmentioning
confidence: 99%
“…These enzymes may also be involved in the initiation of digestion of food components in the oral cavity. The other major category of proteins identified were the transport/carrier proteins apolipoprotein B (APOB), albumin (ALB) and apolipoprotein H (APOH) that might have been detected in saliva through leakage from blood [34,35]. Calcium binding proteins such as calmodulin-like (CALML5), calcium binding protein 39 (CAB39), members of S100 family (S100A7, S100A8, S100A9, S100A11) and annexin family members (ANXA1, ANXA2, ANXA3) were also identified in saliva.…”
Section: Biological Process and Subcellular Localization Of Human Salmentioning
confidence: 99%
“…Saliva is also a rich source of microorganisms, including viruses, bacteria, and fungi, whose composition may serve as a window into the overall health status of an individual. Comprehensive reviews of adult saliva have been previously written and can be found elsewhere (Lawrence 2002;LlenaPuy 2006;Tiwari 2011;Cuevas-Có rdoba and Santiago-García 2014).…”
Section: Saliva As a Biofluidmentioning
confidence: 99%
“…The majority of the published nutritional metabolomics studies focus on urine samples [16 ], but recently Hanhineva et al [21 ] demonstrated the impact of dietary intervention also on the metabolic profile in fasting plasma, and fecal metabolome has been also investigated to evaluate the effect of specific food [36]. Other organic fluids, that is, saliva [37] and the cerebrospinal fluid [38], have been used in humans and animals. Anyway, most studies investigating human metabolomics measurements are limited to a single biofluid, while an approach to generate an integrated picture of metabolomics associations over multiple fluids would be needed.…”
Section: The Genetic Influences On Metabolic Phenotypesmentioning
confidence: 99%